2003
DOI: 10.1080/02724980244000206
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Reader Skill on Phonological processing in visual Word Recognition

Abstract: There has been much debate about the role of phonology in reading. This debate has been fuelled, in part, by mixed findings for phonological effects in lexical decision tasks. In the present research we investigated the impact of reader skill on three phonological effects (homophone, homograph, and regularity effects) in a lexical decision task and in a phonological lexical decision task. In both tasks, the more skilled readers showed different patterns of phonological effects from those of the less skilled re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 46 publications
1
48
1
1
Order By: Relevance
“…They measured participants' exposure to print using the Author Recognition Test (Stanovich & West, 1989) and also examined the efficiency of participants' orthographic and phonological processing in visual word recognition tasks. The results showed that participants with high levels of print exposure were able to make faster and more accurate lexical decisions and to process orthographic and phonological information more efficiently than participants with lower levels of print exposure (for similar conclusions, see Unsworth & Pexman, 2003). The results of two other studies with undergraduate samples, however, suggested that the effects of experience are more limited.…”
mentioning
confidence: 48%
“…They measured participants' exposure to print using the Author Recognition Test (Stanovich & West, 1989) and also examined the efficiency of participants' orthographic and phonological processing in visual word recognition tasks. The results showed that participants with high levels of print exposure were able to make faster and more accurate lexical decisions and to process orthographic and phonological information more efficiently than participants with lower levels of print exposure (for similar conclusions, see Unsworth & Pexman, 2003). The results of two other studies with undergraduate samples, however, suggested that the effects of experience are more limited.…”
mentioning
confidence: 48%
“…Indeed, phonological information is activated routinely during the visual presentation of words and pseudowords (e.g. Naish, 1980;Perfetti, Bell, & Delaney, 1988;Perfetti & Bell, 1991;Van Orden, Johnston, & Hale, 1998;Lukatela & Turvy, 1994 a&b;Lukatela, Frost, and Turvey, 1999;Unsworth & Pexman, 2003). If a visual encounter with an unknown word also activates pronunciations, the memory trace of this encounter may include both orthographic and phonological information.…”
Section: Differences Between Print and Speech In Learning New Wordsmentioning
confidence: 99%
“…However, several factors must be considered when studying homophone effects during lexical decisions, including: the frequency of the homophone, the orthographic characteristics of non-word trials, the phonological nature of the non-words used, task demands, and reading and phonological skills (Holyk & Pexman, 2004;Pexman, Lupker, & Jared, 2001;Unsworth & Pexman, 2003), all of which not only underlie the homophone effect but might also be relevant to word recognition, which occurs in a very short lapse. Thus, it may be important to determine whether slow-naming children have difficulties in storing orthographic memory representations or in automatizing those representations when discriminating pseudohomophones from real words.…”
Section: Introductionmentioning
confidence: 99%